Smart Agriculture: IoT-Based Automation and Monitoring for Enhanced Farming Efficiency - Vijayshankar Singh; Akansha Bhingare; Vrushabh Dhamne; Sanjay Jadhav (International Journal of Electronics Automation, 2024)
This paper presents the development of an innovative agriculture automation and monitoring system designed to improve farming efficiency through the integration of low-cost sensors and microcontrollers. The system utilizes components such as PIR motion sensors, soil moisture sensors, DHT11 humidity sensors, and a relay motor pump for precise automation of irrigation and environmental monitoring. NodeMCU (ESP8266) acts as the primary controller, facilitating real-time data gathering and decision-making. Results show significant potential for optimizing water usage, soil moisture Reading, and reducing manual labor. The proposed solution incorporates machine learning-based decision-making, enabling adaptive irrigation scheduling based on environmental conditions. Additionally, solar-powered integration enhances energy efficiency, making the system sustainable for remote agricultural regions. Experimental results demonstrate significant improvements in water conservation, optimized soil moisture levels, reduced human intervention, and enhanced crop health. This work contributes to the field of precision agriculture, IoT-driven smart farming, and real-time environmental automation, showcasing the potential for widespread adoption in modern farming practices.
Keywords: Humidity; Soil Moisture; irrigation; sensors; temperature